Spectroscopic characteristics of M2Al2SiO7: Eu (M: Sr, Ca) phosphors - Tiến, Đỗ Thanh; Sơn, Nguyễn Mạnh (Hue University Journal of Science: Natural Science, 2020)
The europium-ion-doped M2Al2SiO7 (M: Ca, Sr) materials with tetragonal phase structure were successfully synthesized by using the solid-state reaction method. The Eu2+-doped M2Al2SiO7 materials emit green radiation. The photoluminescent spectra have a board band, peaking at 510 nm for the Sr2Al2SiO7 phosphor and 521 nm for the Ca2Al2SiO7 phosphor. Meanwhile, the photoluminescent spectra of the Eu3+-doped M2Al2SiO7 material have narrow lines, emitting red radiation. The role of the europium activation centers in the lattice greatly depends on the conditions of the sample preparation. The crystal field effect of Ca2Al2SiO7 lattice acting on Eu2+ ions is stronger than that of Sr2Al2SiO7 lattice.